Sibling Correlations and Social Mobility in Latin America - Alejandro Gaviria; Momi Dahan (Inter-American Development Bank, Office of the Chief Economist, 1999)
In this paper, social mobility is measured by looking at the extent to which family background determines socioeconomic success. Roughly speaking, social mobility can be measure by means of two distinct types of correlations: intergenerational correlations and sibling correlations.
Keywords: 330; Soziale Mobilität; Lateinamerika